Annular pancreas causing extrahepatic biliary obstruction - Ogulin, Mateja (Radiology and oncology (Ljubljana), 2004)
Backgronnd. Annular pancreas is an uncommon congenital abnormality, consistingof a flat band of pancreatic tissue, which encircles duodenum or extrahepatic biliary duct. We present a case of obstructive jaundice, caused by annular pancreas. Case report. A 46 years old female was admitted because of a sudden onset of abdominal pain, vomiting and jaundice. For the last six years she occasionally noticed her skin was light yellow, in the last year shefelt distension in the upper abdomen, especially after fatty meals. Conclusions. Two US examinations, the first one six months before the admission, showed dilated hepatic ducts. The reason of dilatation was unclear,even after the endoscopic US examination. At operation an almost complete obstruction of the common hepatic duct was found, caused by a narrow band of pancreatic tissue.
Keywords: Abnormalities; anomalije; Bile Duct Obstruction, Extrahepatic; Cholangiopancreatography, Endoscopic Retrograde; Holangiopankreatografija endoskopska, retrogradna; Middle Age; Pancreas; Srednja leta; Trebušna slinavka; žolčevod; Žolčevodi, obstrukcija ekstrahepatična